The Global Burden of Motor Neuron Disease: An Analysis of the 2019 Global Burden of Disease Study - Park, Jin; Kim, Jee-Eun; Song, Tae-Jin (Frontiers in Neurology, 2022)
Up-to-date, accurate information on the disease burden of motor neuron disease (MND) is the cornerstone for evidence-based resource allocation and healthcare planning. We aimed to estimate the burden of MND globally from 1990 to 2019, as part of the Global Burden of Disease, Injuries and Risk Factor (GBD) study. Amyotrophic lateral sclerosis, progressive muscular atrophy, primary lateral sclerosis, pseudobulbar palsy, spinal muscular atrophy and hereditary spastic paraplegia- were included for analysis as MNDs. We measured age-standardized incidence, prevalence, death, and disability-adjusted life-years (DALYs) in 204 countries and territories worldwide from 1990 to 2019 using spatial Bayesian analyses. The effects of age, sex, and the sociodemographic index (measures of income per capita, education, and fertility) on incidence, prevalence, death, and disability-adjusted life-years due to MNDs were explored. According to 2019 GBD estimates, there were ~268,673 [95% uncertainty interval (UI), 213,893–310,663] prevalent cases and 63,700 (95% UI, 57,295–71,343) incident cases of MND worldwide. In 2019, MND caused 1,034,606 (95% UI, 979,910–1,085,401) DALYs and 39,081 (95% UI, 36,566–41,129) deaths worldwide. The age-standardized rates of prevalence, incidence, death, and DALYs for MNDs in 2019 were 3.37 (95% UI, 2.9–3.87) per 100,000 people, 0.79 (95% UI, 0.72–0.88) per 100,000 people, 0.48 (95% UI, 0.45–0.51) per 100,000 people, and 12.66 (95% UI, 11.98–13.29) per 100,000 people, respectively. The global prevalence and deaths due to MND in 2019 were increased (1.91% [95% UI, 0.61–3.42] and 12.39% [95% UI, 5.81–19.27], respectively) compared to 1990, without significant change in incidence. More than half of the prevalence and deaths due to MND occurred in three high-income regions (North America, Western Europe, and Australasia). In most cases, the prevalence, incidence, and DALYs of MNDs were high in regions with high sociodemographic index; however, in high-income East Asia, these were relatively low compared to similar sociodemographic index groups elsewhere. The burden of MND increased between 1990 and 2019. Its expected increase in the future highlights the importance of global and national healthcare planning using more objective evidence. Geographical heterogeneity in the MND burden might suggest the influences of sociodemographic status and genetic background in various regions.